Law and economic development: current issues - Batievskaia V. B., Kelekhsaeva M. V., Sitokhova T. E., Minakov A. V., Kruglov V. N., Kiselev A. A., Borovkova V. A., Borovkova V. A., Zolotareva I. V., Airikh G. E., Kurov A. E., Lykova O. A., Siziakina M. S., Soldatova L. I., Shmidt I. I., Shaibakova L. F., Chechulina O. A., Belostotskaia A. A., Shchankina L. N., Garnaia ivanova I. A., Serebrennikova A. V., Burtseva E. V., Medvedeva S. V. (Law and economic development: current issues, 2023)
the study examines the issues of mutual influence of institutional changes and material and technological development of the water transport industry in terms of changes in the conditions of navigation on the inland waterways of Russia. In a historical retrospective, the development of ports is examined depending on the prevalence of certain technologies, a logical relationship is built between the main categories that determine the processes of change in the institutional structure of the economy. The factors influencing the process of transformation of the technological structure of the inland water transport industry in the Azov-Black Sea direction are considered.
Keywords: технологические изменения; технологическая структура; институциональные условия; внутренние водные пути России; Азово-Черноморский бассейн; развитие портов; technological changes; technological structure; institutional conditions; inland waterways of Russia; Azov-Black Sea basin; port development